A Study of Knowledge, Attitudes and Practice of Emergency Contraceptive Pills Among Female College Students in Udaipur, Rajasthan - Kumar, Arun; Keerti; Sharma, Chandra P; Jain, Chetan K (National Journal of Community Medicine, 2012)
Background: Emergency contraception is administered after unprotected intercourse to prevent unintended pregnancy. Sexually active young and adolescent women are at greatest risk of unintended pregnancy and thus unsafe abortion related morbidity and mortality. Objective: Purpose of this study was to evaluate knowledge, attitude and experiences on emergency contraceptive pill (ECP) by female college students of Udaipur. Study design: Cross-sectional, pre-structured questionnaire based study. Material and methods: Study was conducted among 600 college going female students (arts, science and commerce faculty) of two randomly selected girls colleges of Sukhadia University Udaipur. Data were analyzed statistically by simple proportions and test of significance (Chi square test) and Mann Whitney U test using SPSS ver.16. Results: Students included in study were of 16-29 years age group (mean age 18.6±3.2 years), 225 (37.5%) had adequate knowledge about emergency contraceptive pills, statistically significant difference in knowledge is seen among students who got knowledge from literary sources and health personnel (p<0.05). Majority of the science stream students (50%) were having adequate knowledge followed by commerce and arts stream students respectively but statistically significant difference in knowledge is seen among all faculty students(p<0.05). Majority of students (78%) know about the correct timing of EC pills administration. Among all the students only 201 (33.5%) students shown positive attitude regarding EC pills. No significant association seen between adequate knowledge and positive attitude (p>0.05).Only 3% students had already used EC pills. Conclusion: Awareness of EC pills is low and there is a gap between knowledge and attitude. Appropriate awareness programme needed.